Facilitators and barriers to scaling-up integratedcare for arterial hypertension and type 2 diabetes in Slovenia - Zavrnik, Črt (Zdravstveno varstvo, 2024)
Introduction: Arterial hypertension and type 2 diabetes are significant contributors to global non-communicabledisease-related mortality. Integrated care, centred on person-centred principles, aims to enhance healthcare qualityand access, especially for vulnerable populations. This study investigates integrated care for these diseases in Slovenia,providing a comprehensive analysis of facilitators and barriers influencing scalability.Methods: Qualitative methods, including focus group discussions and semi-structured interviews, were employed in linewith the grounded theory approach. Participants represented various levels (micro, meso and macro), ensuring diverseperspectives. Data were collected from May 2019 to April 2020, until reaching saturation. Transcripts were analysedthematically using NVivo software.Results: Nine categories emerged: Governance, Health financing, Organisation of healthcare, Health workforce, Patients,Community links, Collaboration/Communication, Pharmaceuticals, and Health information systems. Some of identifiedbarriers were political inertia and underutilisation of research findings in practice; outdated health financing system;accessibility challenges, especially for vulnerable populations; healthcare workforce knowledge and burnout; patients’complex role in accepting and managing their conditions; collaboration within healthcare teams; and fragmentation ofhealth information systems. Peer support and telemedicine were the only two potential solutions identified.Conclusions: This study offers a comprehensive evaluation of integrated care for hypertension and type 2 diabetesin Slovenia, featuring insights into facilitators and barriers. These findings have implications for policy and practice.Monitoring integrated care progress, refining strategies, and enhancing care quality for patients with these two diseasesshould be priorities in Slovenia.
Keywords: arterijska hipertenzija; barriers; facilitators; hypertension; integrated care; integrirana oskrba; ovire; priložnosti; sladkorna bolezen tipa 2; type 2 diabetes